(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study investigates a number of issues related to the differences between young and adult second language learners concerning the process of parameter resetting in cases when the first and the second language have two different values of the same parameter. The case which is examined in this study is the fact that Arabic which is the first language of the target groups of participants in this study is a pro-drop (null-subject) language, while English which they are studying as a foreign language is a non-pro- drop (non-null subject) language. The study uses Grammaticality Judgment tasks to which group of the Libyan EFL learners, the young or the adult learners’ group have reset this parameter from its value in Arabic to its different value in English. These Grammaticality Judgment tasks were applied to 91 university students who are studying in the Department of English, Faculty of Arts at Misurata University. The young learners’ group included 45 pupils in the first grades at the International Knowledge School in Misurata. The academic performance level of the participants in the two groups was considered as a factor which may affect the grammaticality judgments of the participants. The results showed that younger learners performed better in the grammaticality judgment tasks and that their judgments were not affected by the fact that their first language had a different value of the pro-drop parameter. It was also noticed that the intensive academic study at a university level did not help the older participants to be better than younger participants in this task. Moreover, the level of academic achievement was not a factor in this study that participants with lower academic levels performed better than those with higher academic levels